High strain response and low hysteresis in BaZrO3-modified KNN-based lead-free relaxor ceramics - Zhang, Jian; Liu, Zixuan; Zhang, Tao; Liu, Yunfei; Lyu, Yinong (Journal of materials science. Materials in electronics, 2021)
The high driving electric field and the large strain hysteresis are subject to a challenge for piezoelectric actuators’ practical applications. In order to obtain the piezoceramics with giant strain and low hysteresis at small electric field, a ternary solid solution (0.97- x )(K 0.48 Na 0.52 )Nb 0.965 Sb 0.035 –0.03Bi 0.5 (K 0.18 Na 0.82 ) 0.5 ZrO 3 - x BaZrO 3 ( x = 0–0.06) was designed and synthesized by the traditional solid-state reaction method. The relationships among phase transition, microstructure, and electrical properties of the ceramics samples were systemically investigated. Under a low electric field of 4 kV/mm, the ceramic with x = 0.02 obtained a high bipolar strain of 0.29% ( S max / E max = 729 pm/V) and a low hysteresis of 13.8%. The excellent piezoelectric properties are mainly attributed to rhombohedral–orthorhombic–tetragonal (R–O–T) phase boundary and the relaxor-to-ferroelectric phase transition. We believe that our research can not only provide the pathway of achieving KNN-based ceramics with high strain and low hysteresis but also promote the practical application of lead-free piezoelectric actuators.